Brief Report: Association of Genetic Variants in the IL4 and IL4R Genes With the Severity of Joint Damage in Rheumatoid Arthritis: A Study in Seven Cohorts. Issue 12 (December 2013) - Krabben, A.; Wilson, A. G.; de Rooy, D. P. C.; Zhernakova, A.; Brouwer, E.; Lindqvist, E.; Saxne, T.; Stoeken, G.; van Nies, J. A. B.; Knevel, R.; Huizinga, T. W. J.; Toes, R.; et al.
<x xml:space="preserve">Abstract</x> Objective The progression of joint destruction in rheumatoid arthritis (RA) is determined by genetic factors. Changes in IL4 and IL4R genes have been associated with RA severity, but this finding has not been replicated. This study was undertaken to investigate the association between IL4‐ and IL4R‐tagging single‐nucleotide polymorphisms (SNPs) and the progression rate of joint damage in RA in a multicohort candidate gene study. Methods IL4‐ and IL4R‐tagging SNPs (n = 8 and 39, respectively) were genotyped in 600 RA patients for whom 2, 846 sets of radiographs of the hands and feet were obtained during 7 years of followup. Subsequently, SNPs significantly associated with the progression of joint damage were genotyped and studied in relation to 3, 415 radiographs of 1, 953 RA patients; these included data sets from Groningen (The Netherlands), Lund (Sweden), Sheffield (UK), the North American Rheumatoid Arthritis Consortium (US), Wichita (US), and the National Data Bank (US). The relative increase in progression rate per year in the presence of a genotype was determined in each cohort. An inverse variance weighting meta‐analysis was performed on the 6 data sets that together formed the replication phase. Results In the discovery phase, none of the IL4 SNPs and 7 of the IL4R SNPs were significantly associated with the joint damage progression rate. In the replication phase, 2 SNPs in the IL4R gene were significantly associated with the joint damage progression rate (rs1805011 [P = 0.02] and rs1119132 [P = 0.001]). Conclusion Genetic variants in IL4R were identified, and their association with the progression rate of joint damage in RA was independently replicated.